2017
DOI: 10.1186/s40463-017-0238-7
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal Parathyroidectomy and Relocation of the Parathyroid Remnant for Renal Hyperparathyroidism: Modification of a traditional operation

Abstract: BackgroundWe describe a modification of the conventional subtotal parathyroidectomy operation where the parathyroid gland(s) remnant is repositioned with intact vascular supply to a plane superficial to the infrahyoid strap muscles and immediately under the skin incision. This technique called Subtotal Parathyroidectomy and Remnant Relocation (SPARE) retains all the metabolic advantages of the conventional operation with the added advantage of easier identification of a recurrent hyperplastic remnant if re-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The former mainly involves subtotal resection or total parathyroid resection + autologous transplantation combined with double neck exploration, whereas the latter mainly involves single-gland resection. [ 9 ] Therefore, more accurate preoperative positioning and a precise qualitative diagnosis are required to select surgical methods to reduce or avoid postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The former mainly involves subtotal resection or total parathyroid resection + autologous transplantation combined with double neck exploration, whereas the latter mainly involves single-gland resection. [ 9 ] Therefore, more accurate preoperative positioning and a precise qualitative diagnosis are required to select surgical methods to reduce or avoid postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…SPTX is a relatively old surgical method, in which the parathyroid gland weighing 40-50 mg is preserved (13), but this method has been criticized by some experts due to the high recurrence rate (14). In recent years, some studies have reported that the efficacy of removal of 3 parathyroid glands plus 3/4-7/8 of remaining parathyroid gland is superior to that of traditional method (15). There is still no consensus on this issue in China, and the size of residual parathyroid gland ranges from 1/8 to 1/2 of the smallest parathyroid gland (16).…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have proposed the “subtotal parathyroidectomy and relocation of remnants,” which refers to the removal of all hyperplastic parathyroid glands and repositioning of a small portion (50 mg) of vascularized parathyroid tissue on the muscular surface of the subhyoid band, below the skin incision, which has a good supply of blood vessels. This not only preserves the ability of the residual glands to continue to secrete PTH and reduces the probability of postoperative complications, but also does not require re-exploration after recurrence, and thus, avoids damage to the recurrent laryngeal nerve ( 56 ).…”
Section: Treatment For Hptmentioning
confidence: 99%